2013
DOI: 10.2478/s11536-012-0123-8
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response association between physical activity and metabolic syndrome

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…Dallongeville et al [41] has further suggested that MetS is a contributor to the familial aggregation of premature CVD independently of other classical cardiovascular risk factors. Furthermore, a higher frequency of MetS among sedentary subjects in the present study was found supported by Baceviciene et al [42]. Similarly, Edwardson et al [43] has observed that greater time spent sedentary increases the MetS odds with no differences for subgroups of sex, sedentary behavior measure, MetS definition, study quality or country income.…”
Section: Discussionsupporting
confidence: 87%
“…Dallongeville et al [41] has further suggested that MetS is a contributor to the familial aggregation of premature CVD independently of other classical cardiovascular risk factors. Furthermore, a higher frequency of MetS among sedentary subjects in the present study was found supported by Baceviciene et al [42]. Similarly, Edwardson et al [43] has observed that greater time spent sedentary increases the MetS odds with no differences for subgroups of sex, sedentary behavior measure, MetS definition, study quality or country income.…”
Section: Discussionsupporting
confidence: 87%
“…Another possible explanation for the gender difference is there may be a threshold for MVPA above which MetS risk is reduced and these Yakut women were not sufficiently active to reach the threshold. Yet a previous study in an urban Lithuanian population found a linear dose-response between physical activity and MetS rather than a threshold effect (Baceviciene et al, 2013). The state of the evidence is not sufficient to understand this relationship, particularly in transitioning populations.…”
Section: Gender Differencesmentioning
confidence: 82%
“…Physical activity leads to improvements in the cardio-metabolic profile (Ertek and Cicero, 2012) and reduces the potential of clustering of risk factors (Baceviciene et al, 2013;Das et al, 2012;Janseen and Ross, 2012). SB, which can also be considered physical inactivity or very low physical activity, leads to worsening of the cardio-metabolic profile (Healy et al, 2011;Saunders et al, 2012) and increases the chances of risk factor clustering (Edwardson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In general, higher adherence levels of total or recreational PA were more strongly associated with the MHO phenotype. Indeed, an inverse association between leisure-time [ 28 ] and transportation-related PA [ 29 , 30 ] and MetS has also been shown, and obese individuals who engage in transportation PA are also more likely to be metabolically healthy [ 27 ]. In the present study, no participants were sufficiently active based on transportation PA alone to be considered for separate analysis.…”
Section: Discussionmentioning
confidence: 99%